Rancang Bangun Sistem Penghitung Jumlah Orang Melewati Pintu menggunakan Sensor Infrared dan Klasifikasi Bayes - Raden Galih Paramananda; Hurriyatul Fitriyah; Barlian Henryranu Prasetio (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The growing of visitor number lead to a new problem that is, the fullness of the place when the visitors is not comparable with the available standard capacity of the building. Counting the number of visitors in a shopping center can provide an information for the manager to optimizing the place, as well as to evaluating the attraction in some shopping areas. Area managers can analyze and monitor the center state of the crowd. From this problem, it is need an automate system to calculate the visitor who passes through the door simultaneously. In this study, the parameter that used by reseaecher is the detection of passing objects. The researcher used infrared sensor switch E18-D80NK that will be processed used Bayes classification to calculate the total of visitor who passes through the sensor in the door. The Bayes method was chosen as one of the techniques for decision-making classification counters of people who passing through the door simultaneously, this method is one of the classification method is quite simple and easy to be understood. So the accuracy obtained by this system using Bayes method is 79.24%. In this case, reseacher using the door size width of 200 cm and 190 cm high with the computation time of sensor readings until the calculation of 679.2 ms or about 0.6792 seconds.